The role of modern academic libraries: survey of perceptions and experiences of graduate students in social sciences and humanities (Libellarium: journal for research in the field of information and related sciences, 2016)
Contemporary academic libraries have experienced profound changes lately under the influence of information and communication technology and changed approaches to teaching and learning. If academic libraries are to remain integral parts of educational experience of students, librarians and managers of academic institutions need to think anew their physical and virtual spaces and servicesThe paper presents results of a survey which aimed to investigate the perceptions and experiences of graduate students in humanities and social sciences regarding physical and virtual library spaces and services, and to assess their satisfaction with them.Results of the study show that the largest number of respondents ue their academic library regularly (several time a month or week) and that more than half consider physical library spaces and services important for their successful learning. Interestingly, students reported that electronic library sources are more important to them than physical library spaces and services, although they prefer print material over electronic sources of information. Respondents had split opinions regarding their favourite learning place in the library: slightly more respondents preferred silent reading room over the group study room. The study has shown that perception adn use of academic library is influenced by gender, academic success and personal approach to the studying.
Keywords: academic libraries; physical space; graduate students; library services; e-sources; social sciences and humanities; Faculty of Humanities and Social Sciences in Osijek